PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN LIMBAH PERANTINGAN PEPOHONAN DI LINGKUNGAN PERUMAHAN - Dwi Haryanta; Tatuk Tojibatus Sa’adah; Ristani Widya Inti (Yayasan Education and Social Center, 2022)
Urban forest development programs, urban parks and tree planting in residential require tree maintenance to keep the view beautiful and not dangerous in case of rain. Tree pruning waste in residential areas poses environmental and social problems. Community empowerment activities at RW 02 Kalirungkut Surabaya aim to provide knowledge on how to manage tree pruning waste that is processed into useful compost in urban farming practices. The community empowerment program in managing tree pruning waste uses the Participatory Rapid Rural Appraissal and Rapid and Rural Appraissal methods. Inventory of problems and formulation of solutions is carried out in a short time but studies are carried out in depth and the community is directly involved in the preparation of implementation plans and evaluation of activities. The community of RW 02 Kalirungkut Surabaya was very enthusiastic in implementing the program and within 3 months the problem of disposing of waste tree pruning was resolved, and the community was able to harvest 15 cubic meters of compost. The community realizes that tree pruning waste can be used as compost which has economic value as an income for RW 02 Kalirungkut and can meet the compost needs for people who are practicing urban farming